Pattern of abdominal wall hernia attended in Fishtail Hospital, Pokhara, Nepal - Ghimire, Pradeep; Timilsina, Bishowdeep (Journal of Chitwan Medical College, 2018)
Introduction: All hernias are caused by a combination of pressure and an opening or weakness of muscle or fascia. The pressures push an organ or tissue through the opening or weak spot. Sometimes muscle weakness is present at birth; more often it occurs later in life. Abdominal wall hernias occur only at sites at which the aponeurosis and fascia are not covered by striated muscle. The aim of the study was to know different pattern of abdominal hernias, to analyze various clonal and demographic profiles of various abdominal wall hernias presenting to the mid-western part of Nepal and to evaluate different types of operation and complication performed in hernias patients. Methods: Hospital based retrospective descriptive study performed in Fishtail Hospital and Research Centre, Pokhara Nepal in October 2012 to July 2017. Ethical clearance was taken from institute and written consent was taken from all the patients who are involved in the study. All sociodemographic data were collected and analyzed by using SPSS 20 statistical software. Results: In this study period, 492 patients of various types of hernias were operated by various methods. Most common type of hernia is indirect inguinal hernia (94.39%) and one rare spigelian hernia was also there. Right inguinal hernia was more common (58.42%). Conclusion: Inguinal Hernia was the commonest type of hernia (394, 90.3%). Among inguinal hernia right side was more common (58.42%). Among inguinal hernias, most of the hernias were found in 0-9 years (38.21%). In this study we found recurrence rate 1.4%.